ANALISIS YURIDIS TERHADAP PEMBATALAN HAK ASUH ANAK OLEH PENGADILAN AGAMA (STUDI PUTUSAN PENGADILAN AGAMA NO. 5/Pdt.G/2006/PA.MDN) - RAHMI FADHILAH HARAHAP (PREMISE LAW JURNAL, 2016)
A child is the world’s life ornament who becomes the parents’ pride as it is stated in Al-Quran (QS, AL-Kahfi:46), “Wealth and children are an ornament of life of the world. But the good deeds which endure are better in thy Lord’s sight for reward, and better in respect of hope”; therefore, we have to obey the command of Allah to take care, raise, and educate our children. The research was judicial normative and descriptive analytic, based on general legal theory which was applied to explain a set of other data. The theory used in the research was the theory of legal protection for under-aged children (before mummayiz), looked after by their guardian. The cancellation of the right to look after under-aged children is because the parensts are considered not legally capable so that the judge abolishes their rights, the judge appoints the priority of the family who has the rights to look after under-aged children. It is recommended that psychological factor and the security of the children who are looked after by their guardian should be considered, the Religious Court’s Ruling should be implemented according to the prevailing procedures by putting forward the principle of negotiation and consanguinity in the transferring of the rights. Keywords: The Right to look After, Orphans, Islamic Law